2010
DOI: 10.1073/pnas.1005484107
|View full text |Cite
|
Sign up to set email alerts
|

Long-lived quantum coherence in photosynthetic complexes at physiological temperature

Abstract: Photosynthetic antenna complexes capture and concentrate solar radiation by transferring the excitation to the reaction center that stores energy from the photon in chemical bonds. This process occurs with near-perfect quantum efficiency. Recent experiments at cryogenic temperatures have revealed that coherent energy transfer-a wave-like transfer mechanism-occurs in many photosynthetic pigment-protein complexes. Using the Fenna-MatthewsOlson antenna complex (FMO) as a model system, theoretical studies incorpor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

52
1,138
5
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 988 publications
(1,197 citation statements)
references
References 30 publications
52
1,138
5
2
Order By: Relevance
“…The signatures of vibronic coupling in multidimensional spectroscopy have drawn great interest lately, in particular to interpret oscillatory transients observed for light-harvesting complexes [3,[8][9][10] that persist much longer than predicted electronic dephasing times [11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The signatures of vibronic coupling in multidimensional spectroscopy have drawn great interest lately, in particular to interpret oscillatory transients observed for light-harvesting complexes [3,[8][9][10] that persist much longer than predicted electronic dephasing times [11].…”
Section: Resultsmentioning
confidence: 99%
“…For FMO, the oscillations were found to persist for hundreds of femtoseconds at ambient temperatures and even up to a few picoseconds at 77 K [10]. In contrast, the measured spectral linewidths predict electronic dephasing times at 77 K hardly exceeding 100 fs [11], owing to rapid, stochastic variations in the environment, and coherences between excitons are expected to decay roughly on this timescale.…”
Section: Introductionmentioning
confidence: 83%
“…Quantum coherence in electron transfer in photosynthesis lasts for a long time (600 fs) in the pigment-protein complex (Engel, 2007;Ishizaki, 2010). But it is not yet fully known how this coherence is brought about in living tissue, although it has been shown that environmental noise increases energy delivery efficiency (Panitchayangkoona, 2010;Collini, 2010). The inferred algorithm of the present study shows that this coherence may be embedded in both higher and lower frequency bands.…”
Section: Photosynthesismentioning
confidence: 99%
“…4 On top of the relaxation process, oscillatory components prevail in 2d-spectra which contain signatures of electronic coherences and specific vibrational modes. 6,[8][9][10] The coupling to the environment determines the transfer efficiency in LHCs 11,12 through the bath-correlation time of the phonon bath, [13][14][15] the shape of the continuum part of the spectral density, 9,16 and specific structures within the spectral density. 9,17 For the FMO complex, the superohmic character of the spectral density results in long-lasting electronic coherences despite a strong coupling to the environment.…”
Section: Introductionmentioning
confidence: 99%